How does hostile resistance interfere with the benefits of cognitive–behavioral therapy for panic disorder? The role of therapist adherence and working alliance. (17th November 2022) - Schwartz, Rachel A.; McCarthy, Kevin S.; Solomonov, Nili; Chambless, Dianne L.; Milrod, Barbara; Barber, Jacques P.
Abstract: Objective Although clients' hostile behavior directed at therapists ( hostile resistance ) predicts worse outcomes in cognitive–behavioral therapy (CBT) for panic disorder, the process by which this happens remains unknown. This study examines two putative mechanisms: working alliance and therapist adherence. Method: Seventy-one adults with primary panic disorder received CBT in a larger trial. Hostile resistance and adherence in Sessions 2 and 10 were reliably coded using observer-rated measures; client- and therapist-rated questionnaires assessed working alliance. Outcome measures were attrition and symptomatic improvement, assessed at multiple timepoints with the Panic Disorder Severity Scale. Results: Hostile resistance was significantly related to both preexisting ( r   = −.36, p   =  .04) and subsequent declines ( r   = −.58, p   <  .0001) in the working alliance. Nevertheless, hierarchical linear modeling revealed that neither a declining alliance nor therapist adherence (whether treated as linear or curvilinear) was independently predictive of symptom change, nor did these factors mediate hostile resistance's association with worse symptomatic improvement. Exploratory logistic regressions similarly indicated that neither adherence nor alliance moderated whether hostilely resistant clients dropped out. Conclusion: This is the first study to establish a bidirectional association between hostile resistance and a declining working alliance. Findings also add to a mixed literature on the adherence-outcome relationship.